Synesthesia in Studies of Art. Specifying the Term - Alekseeva, Anna V. (Actual Problems of Theory and History of Art, 2013)
The article touches on the problem of the term “synesthesia” in the culturological meaning in the modern studies of art. Misunderstanding between psychological and culturological disciplines and the invalidity of the term in the culturological meaning by European and American psychologists make this article significant. The goal of this article is to substantiate the use of alternative terms within the meaning of “synesthetic” type of art works.
Keywords: synesthesia in art; colour music; cross-modal binding in art; intermodal analogies